Evaluation of Energy Input-Output in Wheat Crop Cultivation in Agro-industry Company of Mazare Novin Iranian (Agh Ghalla) - Mohammadali Maysami (Journal of Agricultural Science and Sustainable Production, 2020)
Abstract Background & Objective: Energy efficiency in wheat cultivation in agro-industry Company of Mazrae Novin Iranian (Agh Ghalla in Golestan province, Iran) was investigated. The aim was comparison of the wheat production method in this company, according to calculated energy efficiency indices, with reported values from other places.   Materials &Methods:The company has four units each with an area of 323, 59, 857 and 673 ha, namely A, B, C and D units, respectively. These units were categorised according to their location and farms integration. All farms were rain-fed. Energy efficiency indices were calculated according to direct culled data from each unit.   Results: The weighted average of energy input for farms was estimated to be 31.7 GJ.ha-1. Almost 60% of the energy input was indirect energy (in the form of fertilizers, seed, pesticides and machinery) and 40% was direct energy input from tractor fuel. The weighted average for grain yield in farms was 2244 kg.ha-1. The energy intensity of only grain production was 14.12 MJ.kg-1. This high energy intensity results from extra high inputs to achieve the mentioned high yield from rain-fed farms. By converting the grain yield to energy equivalent, the energy output/input ratio was about 1.04 MJ.MJ-1.   Conclusion: Optimisation of nitrogen fertiliser consumption and reduction of machinery operations make opportunities to reduce energy input in company's rain-fed farms without reducing the grain yield. The use of straw as the by-product should be considered by the company.